Serum testosterone and oestradiol predict the growth response during puberty promoting treatment. (1st October 2021) - Huttunen, Heta; Varimo, Tero; Huopio, Hanna; Voutilainen, Raimo; Tenhola, Sirpa; Miettinen, Päivi J.; Raivio, Taneli; Hero, Matti
Abstract: Objective: The influence of androgens and oestrogens on growth is complex, and understanding their relative roles is important for optimising the treatment of children with various disorders of growth and puberty. Design: We examined the proportional roles of androgens and oestrogens in the regulation of pubertal growth in boys with constitutional delay of growth and puberty (CDGP). The study compared 6‐month low‐dose intramuscular testosterone treatment (1 mg/kg/month; n  = 14) with per oral letrozole treatment (2.5 mg/day; n  = 14) which inhibits conversion of androgens to oestrogen. Patients: Boys with CDGP were recruited to a randomized, controlled, open‐label trial between 2013 and 2017 (NCT01797718). Measurements: The patients were evaluated at 0‐, 3‐ and 6‐month visits, and morning blood samples were drawn. Linear regression models were used for data analyses. Results: In the testosterone group (T‐group), serum testosterone concentration correlated with serum oestradiol concentration at the beginning of the study and at 3 months, whereas in the letrozole group (Lz‐group) these sex steroids correlated only at baseline. Association between serum testosterone level and growth velocity differed between the T and Lz groups, as each nmol/L increase in serum testosterone increased growth velocity 2.7 times more in the former group. Serum testosterone was the best predictor of growth velocity in both treatment groups. In the Lz‐group, adding serum oestradiol to the model significantly improved the growth estimate. Only the boys with serum oestradiol above 10 pmol/L had a growth velocity above 8 cm/year. Conclusions: During puberty promoting treatment with testosterone or aromatase inhibitor letrozole, growth response is tightly correlated with serum testosterone level. A threshold level of oestrogen appears to be needed for an optimal growth rate that corresponds to normal male peak height velocity of puberty. Serum testosterone 1 week after the injection and serum testosterone and oestradiol 3 months after the onset of aromatase inhibitor treatment can be used as biomarkers for treatment response in terms of growth.